Comparing two efficiency calibration methods used in gamma spectrometry - Mauz, B.; Hubmer, A.; Bahl, C.; Lettner, H.; Lang, A. (Ancient TL, 2021)
The recent inter-laboratory comparison study revealed considerable differences between laboratories for activity concentrations of U, Th and K. One reason for these differences could be materials and methods employed for calibrating the detector’s efficiency. To address this, we determined the activity concentrations of unknown samples originating from variable geochemical environments using two different efficiency calibration methods: one is based on the direct comparison with the non-certified Volkegem internal standard and the other one uses a certified multi-nuclide reference solution and correction factors for full-energy efficiency, emission probability, true coincidence summing and for sample density. The comparison is based on the hypothesis that consistency between the two methods raises the probability that the activity concentrations determined are accurate. We show here that agreement between the two methods is obtained when the Volkegem activity reference values of 40K and 238U-series are raised by 9%. For the 232Th-series agreement is obtained for the two photon peaks at 338 keV and 911 keV when deploying the published activity reference value. We conclude that the efficiency calibration method should not account for more than 10% variability and cannot be the sole reason for the alarming differences revealed by the inter-laboratory comparison study.